A new method for correcting characteristic curves for centrifugal compressors. (2018) - Chang, Haijun; Wu, Changchun
In gas pipeline industry, a centrifugal compressor's performance is often tested in the factory under specified condition and formulated as performance map before it is offered to its buyer. Concerned performances include head, efficiency and so on. A compressor's original head or efficiency characteristic curve may deviate from its actual one because of various reasons after it runs in field for a period of time. So correction is needed before these characteristic curves are used for simulation, optimisation or other applications. A compressor's actual head and efficiency are extracted from its operating records and used for correction. The correction method is designed according to the idea to move a compressor's characteristic curves to best fit its actual performance. Two different types of compressors operated on Central Asia – China gas pipeline are utilised to test the proposed method and satisfactory results are got.